ANALYSIS OF THE SIGNAL TO NOISE RATIO IN USE OF 15% KVP RULE METHOD IN THE RADIOGRAPHY EXAMINATION SUPINE AP CHEST - Sutoro, Shinta Gunawati; Irsal, Muhammad; Budiati, Tri Asih; Yansyah, Andri (Indonesian Physical Review, 2022)
The exposure factor is one of the important parameters in optimizing the radiographic examination. This study aimed to analyze the value of the Signal To Noise Ratio (SNR) against the use of the 15% kV rule method in the examination of Chest AP Supine. Descriptive quantitative research method conducted in the laboratory of the Department of diagnostic imaging and radiotherapy, Health Polytechnic of the Ministry of Health, Jakarta 2, using computer radiography, X-rays, piranha radiation detectors, and anthropomorphic phantoms, with statistical analysis of the Pearson test to determine the level of relationship between SNR and Exposure Index (EI). Against the 15% kV rule method, then the one-way ANOVA test to determine the effect of the 15% method on changes in value. The results of the Pearson test obtained a p-value of 0.820 with a strong relationship between SNR and EI against the 15% kV method. Therefore, using an exposure factor of 15% kV rule method makes it possible to control the SNR and EI values. The one way ANOVA test has a p-value of 0.943, so there is no significant difference in the SNR value to changes in the exposure factor with the 15% kV rule method so that the optimization of the exposure factor with the 15% kV rule method can reduce the radiation dose while maintaining the image quality radiographic